Plant ecdysteroids: plant sterols with intriguing distributions, biological effects and relations to plant hormones - Tarkowská, Danuše; Strnad, Miroslav (Planta, 2016)
MAIN CONCLUSION: The present review summarises current knowledge of phytoecdysteroids' biosynthesis, distribution within plants, biological importance and relations to plant hormones. Plant ecdysteroids (phytoecdysteroids) are natural polyhydroxylated compounds that have a four-ringed skeleton, usually composed of either 27 carbon atoms or 28-29 carbon atoms (biosynthetically derived from cholesterol or other plant sterols, respectively). Their physiological roles in plants have not yet been confirmed and their occurrence is not universal. Nevertheless, they are present at high concentrations in various plant species, including commonly consumed vegetables, and have a broad spectrum of pharmacological and medicinal properties in mammals, including hepatoprotective and hypoglycaemic effects, and anabolic effects on skeletal muscle, without androgenic side-effects. Furthermore, phytoecdysteroids can enhance stress resistance by promoting vitality and enhancing physical performance; thus, they are considered adaptogens. This review summarises current knowledge of phytoecdysteroids' biosynthesis, distribution within plants, biological importance and relations to plant hormones.
Keywords: rostliny; Plants; Ecdysteroids; regulátory růstu rostlin; ekdysteroidy; Plant Growth Regulators